pengembangan bakat seni di sma negeri 3 gorontalo: pengembangan bakat seni di sma negeri 3 gorontalo - Radhitya Pakudu; Evandri Paputungan; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2022)
Talent is an ability possessed by a person where this ability is inherent in him and can be used to do certain things faster and better than ordinary people. Talent can also be interpreted as an ability that exists within a person from birth where this ability can be used to learn something quickly and with good results. Art is a work created with extraordinary skill, such as drama, dance, music, painting, carving. Everything that is created by humans based on ideas that contain elements of beauty and is able to influence the feelings of others is called art.